2017
DOI: 10.1136/bcr-2017-221567
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre’s syndrome variant of the gut

Abstract: Infectious suppurative thrombophlebitis of the portal venous system, referred to as pylephlebitis, is a rare complication of intra-abdominal inflammatory processes. Advances in diagnostics and antibiotics have improved survival, but mortality remains remarkably high even in the most recent literature. The majority of patients have concomitant bacteraemia on presentation most commonly with typical gastrointestinal (GI) organisms. On rare occasion, patients have culture positive , which has recently been associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…The decision to use anticoagulation must be specific to each patient taking into consideration their individual benefits and risks. Unfortunately, mortality in these cases remains high in spite of advances in diagnostics, sepsis usually being the cause of death [4]. Early recognition and treatment are imperative to patient survival as seen in this case.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The decision to use anticoagulation must be specific to each patient taking into consideration their individual benefits and risks. Unfortunately, mortality in these cases remains high in spite of advances in diagnostics, sepsis usually being the cause of death [4]. Early recognition and treatment are imperative to patient survival as seen in this case.…”
Section: Discussionmentioning
confidence: 90%
“…Treatment is generally with intravenous antibiotics, specifically, a third-generation cephalosporin with metronidazole or monotherapy with a beta lactam/beta lactamase inhibitor or carbapenem for 4 to 6 weeks. Empiric treatment can be given with broad spectrum antibiotics to cover the anaerobes mentioned previously until culture results become available as bacteremia is a common simultaneous occurrence [4]. Management with anticoagulants remains a topic of controversy as there is limited outcomes data and studies on its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though Fusobacterium most commonly causes bacteremia through the oropharynx and internal jugular vein, recent literature has shown that it can readily invade the GI mucosa as well and cause suppurative thrombophlebitis of the portal vein (pylephlebitis) in the setting of an inflammatory process in the gut 3. Our case adds to this evidence and demonstrates how it can also cause septic emboli in the liver and lungs through the portal vein, similar to conventional Lemierre’s syndrome, in which the site of infection is typically the oropharynx and involves the internal jugular vein.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to cause Lemierre’s syndrome, which is characterized by an oropharyngeal infection followed by septic thrombophlebitis of the internal jugular vein with embolization to different organs, including lungs and liver 2. Although Fusobacterium infection originating in the GI tract is rare and seldom reported, it can invade the GI mucosa and cause bacteremia with fatal complications 3-5…”
Section: Introductionmentioning
confidence: 99%